Spatial Analysis of Tourism Climate Comfort in the Belitung Geopark Based on Historical and Projected Climate Data - Aflah Yuliarti; Budhi Setiawan; Mokhamad Yusup Nur Khakim; Presli Panusunan Simanjuntak (Universitas Lambung Mangkurat, 2026)
Climate-based tourism is closely linked to atmospheric comfort, while ongoing global climate change has intensified uncertainty in climatic conditions across many tourism destinations, including tropical geoparks. This study evaluates the spatial and temporal patterns of tourism climate comfort in the Belitung Geopark by integrating historical climate data (1991–2024) and future climate projections (2026–2050) under the Representative Concentration Pathway (RCP) 4.5 scenario. Tourism climate comfort was assessed using the Tourism Climate Index (TCI), which incorporates key meteorological variables, namely air temperature, relative humidity, precipitation, wind speed, and solar radiation. A spatial–temporal analysis supported by Geographic Information Systems (GIS) and heatmap visualization was applied to examine variations across 17 geosites. The results reveal a pronounced seasonal pattern characteristic of tropical climates, with the highest TCI values occurring during the dry season, particularly in August and September. Coastal geosites consistently exhibit higher and more stable comfort levels than inland, hilly, and forested areas, which experience noticeable declines in comfort during the wet season due to increased rainfall and humidity. Climate projections indicate a general reduction in TCI values, especially during transitional and wet months; however, most coastal geosites remain within acceptable to good comfort categories for tourism activities. These findings highlight the role of geographical factors, such as proximity to the coast and local atmospheric dynamics, in shaping spatial variations in tourism climate comfort. The study provides a scientific basis for adaptive tourism management, seasonal tourism planning, and climate change adaptation strategies in tropical geopark destinations, it offers potential applications in geography education and spatial climate analysis.